EXPRESS MODEL FOR WATER TREATMENT PROCESS CALCULATION - Petrenko, V. D.; Netesa, M. I.; Tiutkin, O. L.; Gromova, O. V.; Shynkarenko, V. І.; Kozachyna, V. А. (Science and Transport Progress, 2020)
Purpose. The use of a physical experiment to study mass transfer processes in structures used in water supply and sewage systems requires considerable time and is very expensive. The aim of the work is to develop numerical models for a computational experiment to study the mass transfer process in sand traps. Methodology. For mathematical modeling of the mass transfer process in sand traps, the two-dimensional Navier-Stokes equations and the two-dimensional impurity mass transfer equation are used. For numerical integration of equations describing the motion of a viscous incompressible fluid, implicit difference splitting schemes are used. The unknown parameters at each step of the splitting were found by explicit dependencies. For the numerical integration of the two-dimensional mass transfer equation, an alternately triangular difference splitting scheme is used. Findings. To conduct a computational experiment, a specialized code was created on the basis of the constructed numerical model. The results of computational experiments on the study of mass transfer in sand traps with additional elements are presented. It was determined that water purification efficiency changes with installation of additional elements at the bottom of the sand trap. Originality. The constructed numerical models make it possible to quickly analyze and predict the efficiency of sand traps having a complex geometric shape. They also make it possible to take into account the flow hydrodynamics in the treatment plant. Practical value. The proposed numerical models can be used at the design stage of sewage treatment plants.